1997
DOI: 10.1071/ea97017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil and foliar applications of zinc on cadmium concentration in wheat grain

Abstract: Summary. The effectiveness of foliar applications of zinc sulfate to decrease cadmium (Cd) concentration in wheat grain was assessed at 3 field sites in South Australia—Tumby Bay, Cummins and Keppoch. Foliar zinc (Zn) treatments were found to significantly (P<0.001) decrease Cd concentrations in grain at only 1 site, Tumby Bay. At this site the highest foliar Zn treatment (0.67 kg Zn/ha), which consisted of 2 applications of 0.33 kg Zn/ha applied early and late, decreased the mean Cd concentration in grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
1
13
1
1
Order By: Relevance
“…It has been reported that Zn, Mn, and Cu interfere with the uptake and translocation of Cd [34]. In the present study, Cd application significantly increased leaf/root Cu, Mg, and Fe contents but decreased Zn, Ca, and Mn contents.…”
Section: Se Alleviates CD Toxicity In Tobaccomentioning
confidence: 60%
“…It has been reported that Zn, Mn, and Cu interfere with the uptake and translocation of Cd [34]. In the present study, Cd application significantly increased leaf/root Cu, Mg, and Fe contents but decreased Zn, Ca, and Mn contents.…”
Section: Se Alleviates CD Toxicity In Tobaccomentioning
confidence: 60%
“…Hence, it is likely that these ions reduce Cd uptake to overcome the inhibition. Decreased Cd uptake and accumulation in plants by Zn application were reported (Oliver et al 1997, Koleli et al 2004). Further, competitive interaction between Zn and Cd for uptake to show existence of a common system on plasma membrane was observed (Hart et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reduction of S upon Se addition, in the current study can be ascribed to the competition between Se and S for amino acid, leading to the production of selenocysteine (SeCys), selenomethionine (SeMet), and selenium methylselenocysteine (SeMeSeCys). Additionally, previous reports have shown that Zn, Mn, and Cu interfere with uptake of Cd and translocation from roots to shoots [53]. This affects the rate of metal uptake and distribution, which leads to mineral deficiencies and imbalance in rice.…”
Section: Exogenous Se Counteracts Cd-induced Changes In Nutrientsmentioning
confidence: 98%